1997
DOI: 10.1046/j.1365-4362.1997.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Classic Kaposi's sarcoma in Greece: a clinico‐epidemiological profile

Abstract: CKS in Greece exhibits some special characteristics, including older age of onset; lower male to female ratio; endemic clustering; disseminated skin disease at diagnosis, often accompanied by lymphedema; not unusual visceral or lymph node involvement and association with second malignancies. We suggest that CKS in Greece possibly represents a distinct endemic subtype of CKS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 26 publications
7
37
1
4
Order By: Relevance
“…[14][15][16][17] While Classic Kaposi Sarcoma lesions in this cohort were generally manifest in the lower extremities, followed by the upper extremities and head and neck, our study reveals less upper extremity, lymph node, and visceral sites than previously reported for Classic Kaposi Sarcoma. 1,9,15,17,18 The findings of a large number (n ¼ 15) of Classic Kaposi Sarcoma in the penis in the current study may relate to the previous identification of HHV-8 in semen, even in normal individuals. 19 In comparison, the AIDS-related Kaposi Sarcoma had fewer lower extremity lesions and included more sites highly predictive of HIV infection: that is oral and anogenital.…”
Section: Discussionmentioning
confidence: 53%
“…[14][15][16][17] While Classic Kaposi Sarcoma lesions in this cohort were generally manifest in the lower extremities, followed by the upper extremities and head and neck, our study reveals less upper extremity, lymph node, and visceral sites than previously reported for Classic Kaposi Sarcoma. 1,9,15,17,18 The findings of a large number (n ¼ 15) of Classic Kaposi Sarcoma in the penis in the current study may relate to the previous identification of HHV-8 in semen, even in normal individuals. 19 In comparison, the AIDS-related Kaposi Sarcoma had fewer lower extremity lesions and included more sites highly predictive of HIV infection: that is oral and anogenital.…”
Section: Discussionmentioning
confidence: 53%
“…Bu, kadın hastalarımızın büyük kısmının postmenopozal evrede olması ile açıklanabilir. Yunanistan'da yapılan çalışmada da bizim çalışmamızla benzer şekilde erkek/kadın oranı daha düşük olarak izlenmiştir 17 . Bu, coğrafyamızda hastalığın ayrı bir endemik varyantı ile ilişkili olabileceği gibi hastalığın çevresel faktörlerin etkisiyle klinik seyrinde zamanla oluşabilecek farklılıklar ile de bağlantılı olabilir.…”
Section: Klasik Kaposi Sarkomuunclassified
“…Çeşitli yayınlarda KS'ye özellikle lenfoproliferatif hastalıklar daha sık olmak üzere diğer primer malignitelerin eşlik edebileceği bildirilmiştir 11 . KKS ile sıklıkla ilşkili olan tümörler arasında Hodgkin veya non-Hodgkin lenfoma, kronik lenfositik lösemi, multipl miyeloma, mikozis fungoides, tüylü hücreli lösemi bulunmaktadır 17 . Bizim çalışmamızda bir hastada prostat kanseri ve bir hastada kolon kanseri bulunmaktaydı.…”
Section: Klasik Kaposi Sarkomuunclassified
“…Bone involvement has been reported in some cases of classical KS [2, 3, 4, 5, 6]. The frequency of bone involvement appears to be variable since no case was reported in the series of 67 classical KS of Friedman-Birnbaum et al [1], while 3 cases were reported in the series of 66 cases of Stratigos et al [5].…”
Section: Discussionmentioning
confidence: 99%
“…Extracutaneous lesions are rare in classical KS [1]and bone involvement has rarely been reported [2, 3, 4, 5, 6]. However, bone involvement seems to be more frequent in African KS [7]and AIDS-related KS [8, 9, 10, 11, 12, 13, 14].…”
Section: Introductionmentioning
confidence: 99%